COVID-19 Pandemic and SMEs Performance Decline: The Mediating Role of Management Innovation and Organizational Resilience - Li, Yunjian; Chen, Hongchuan; Wei, Lulu; Wei, Luqing (Frontiers in Public Health, 2022)
It is a major practical problem to find out a pathway for firms to quickly recover from the performance decline in the context of the COVID-19 pandemic and other sudden major crisis in the current academic circles. Based on event system theory and structural adjustment to regain fit model, this paper empirically explores the impact of the COVID-19 pandemic on SMEs performance decline and discusses the management innovation response and organizational resilience mechanism of firms by virtue of the questionnaire survey data of SMEs in Guangdong Science and Technology Park in China. The research results elucidate that the criticality and disruption of the COVID-19 pandemic will not only lead to the SMEs performance decline, but also enable SMEs to carry out management innovation. Moreover, management innovation does not directly curb the SMEs performance decline caused by the COVID-19 pandemic, but indirectly inhibit it by promoting organizational resilience. In other words, the COVID-19 pandemic will indirectly promote organizational resilience through firm management innovation, thereby curbing the SMEs performance decline. A path of management innovation response and organizational resilience to reverse the performance decline can be obtained in the study when SMEs confronting sudden major crisis. Furthermore, the study also expands the application scope of structural adjustment to regain fit model, which provides a useful reference for firm crisis response and sustainable development.